The Theory of Planned Behaviour and the Entrepreneurial Intention of University Students - Bayona-Oré, Sussy (2023)
Businesses generate employment and are recognised as catalysts for the economy. A person who creates and manages a business is an entrepreneur and in a continually changing and complex environment, people capable of creative and innovative thinking will tend to become more entrepreneurial. Running a business successfully requires skills and knowledge, and universities are centres where students can acquire the knowledge and skills that enable them to become entrepreneurs. The purpose of this research was todetermine the effect of attitude (ATT), subjective norms (SN), and perceived behavioural control (PBC) on the entrepreneurial intention (IE) of Peruvian university students enrolled during the period 2019-2020 and pursuing a variety of career paths. This study is quantitative, cross-sectional, and causal. The sample involved 642 students. The Theory of Planned Behaviour (TPB) is used to explain entrepreneurial intention. Confirmatory factor analysis (CFA) was employed for data analysis. The findings show that subjective norms and perceived behavioural control have a positive effect on entrepreneurial intention. Accordingly, it is suggested that the structure of academic programmes be improved to enhance the competencies and skills of future job creators.